The impact of scientific and genre-based approach in english reading comprehension teaching - Maknun, Lu'luil (LPPM Universitas Mercu Buana Yogyakarta, 2019)
The purposes of this study are to determine the more effective approach between: (1) the scientific and conventional approaches, (2) the genre-based and conventional approaches, (3) the scientific and genre-based approaches, (4) the scientific, genre-based and conventional approaches in the teaching of reading comprehension of narrative texts. The research was quasi-experimental with randomized pretest-posttest control group design. The results of the study showed that the implementation of scientific and genre-based approach in reading comprehension teaching leads to better reading comprehension ability of the students. The result proved that students were able to understand the items posttest of narrative texts after 12 meeting of treatments using those approaches and also there were significant difference after conducting treatments. It could be proved from the testing criteria of one-way ANOVA that the null hypothesis (H0) was rejected and Ha was accepted if the value of p (probability) is lower than alpha 5% (0,05), the scientific approach is more effective than the conventional approach in the teaching of reading comprehension of narrative texts with the sig (p) ≤ 0.05, the genre-based approach is more effective than the conventional approach in the teaching of reading comprehension of narrative texts, with sig (p) ≤ 0.05, the scientific approach is more effective than the genre-based approach in the teaching of reading comprehension of narrative texts, with sig (p) ≤ 0.05, and the scientific approach is the most effective of the three approaches under study. The findings revealed the great impact of scientific and genre-based approach, however probably is not significant if it is used in the other setting with the different background of the students.